Analisis Salah Hitung PPH Pasal 21 Pada Karyawan Sudiarta Mart Kabupaten Jembrana - Wiartini, I Gusti Ayu Ketut Alit; Assa’ady, M. Chothibul Umam (CT. Rajawali media Utama, 2024)
The research was conducted to find out more significantly about income tax calculation errors that occur among Sudiarta Mart employees in Jembrana Regency. In this regard, the purpose of the research is to find out more about Income Tax Article 21 which applies to permanent employees of Sudiarta Mart. This research was conducted to find out whether PPH article 21 is also imposed on employees of Sudiarta Mart, Jembrana Regency. This research uses qualitative methods which can be carried out using various methods, such as narrative, phenomenology, document study, observation, interviews, or case studies related to the field of study. Using data from both primary data, secondary data and the results of observations in the field. Based on the research results, there were errors when calculating Pph article 21 for permanent employees, namely lack of updating of employee data, resulting in taxpayers experiencing losses. With an analysis of Article 21 of Income Tax on the company. It is hoped that employee data will always be updated every year.